2020
DOI: 10.1098/rspb.2019.2880
|View full text |Cite
|
Sign up to set email alerts
|

A natural catastrophic turnover event: individual sociality matters despite community resilience in wild house mice

Abstract: Natural disasters can cause rapid demographic changes that disturb the social structure of a population as individuals may lose connections. These changes also have indirect effects as survivors alter their within-group connections or move between groups. As group membership and network position may influence individual fitness, indirect effects may affect how individuals and populations recover from catastrophic events. Here we study changes in the social structure after a large predation event in a populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 54 publications
(85 reference statements)
3
31
0
Order By: Relevance
“…In particular, we asked whether individual monkeys increased their number of social partners or strengthened their existing connections (or both), two strategies that potentially provide different benefits after catastrophic events. 7,22,30 Our results confirmed that rhesus macaques engaged more in affiliative interactions after the storm and that this effect was driven by an increase in their number of partners rather than intensifying existing relationships. These findings motivated us to explore the final two of our five questions: (4) because partner selection might provide critical insights into the function of social relationships, [34][35][36] we asked which partners monkeys associated with after the disaster.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…In particular, we asked whether individual monkeys increased their number of social partners or strengthened their existing connections (or both), two strategies that potentially provide different benefits after catastrophic events. 7,22,30 Our results confirmed that rhesus macaques engaged more in affiliative interactions after the storm and that this effect was driven by an increase in their number of partners rather than intensifying existing relationships. These findings motivated us to explore the final two of our five questions: (4) because partner selection might provide critical insights into the function of social relationships, [34][35][36] we asked which partners monkeys associated with after the disaster.…”
Section: Introductionsupporting
confidence: 75%
“…(2) Whether individuals lost members of their pre-hurricane social network (i.e., a pre-storm grooming partner who died within 6 months after the hurricane). 30,31,33 Although the island did not suffer from mass mortality as a result of the storm, the death rate was higher in the month after the hurricane (October 2017) than in this month in previous years (Figure 1B), which might affect probabilities of affiliation beyond what was expected from normal demographic processes. 31 (3) For the grooming probability model only, whether increased grooming reflected increased use of shared space (i.e., proximity to others) after the disaster.…”
Section: Probability Of Affiliative Interactions Increased After the Hurricanementioning
confidence: 92%
See 1 more Smart Citation
“…2003 ). Predation pressure, however, is unlikely in our system as predators which might be attracted by an aggregation can rarely access the barn (though see: Evans et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Female house mice typically live in social groups with overlapping generations, demic structure and female philopatry (Baker, 1981; Gerlach, 1996; König and Lindholm, 2012; Lewontin and Dunn, 1960). In our study population, groups are relatively stable over time and have proven to be resilient even after a major disturbance (Evans et al, 2020a; Liechti et al, 2020). While there is strong intrasexual female reproductive competition, several females usually breed simultaneously in the same group and even engage in communal offspring care (Ferrari et al, 2019).…”
Section: Introductionmentioning
confidence: 99%